# 相似定理

$\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(at\right)\right\}=\frac{1}{a}F\left(\frac{s}{a}\right)$

$\mathcal{L}\text{\hspace{0.17em}}\left\{\frac{1}{a}f\left(\frac{t}{a}\right)\right\}=F\left(as\right)$

## ■証明

$\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(at\right)\right\}={\int }_{0}^{\infty }{e}^{-st}f\left(at\right)dt$

ここで，$\tau =at$  とおくと， $dt=\frac{1}{a}d\tau$$f\left(at\right)=f\left(\tau \right)$ となり

$\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(\tau \right)\right\}={\int }_{0}^{\infty }{e}^{-\frac{s}{a}\tau }f\left(\tau \right)\text{\hspace{0.17em}}·\text{\hspace{0.17em}}\frac{1}{a}d\tau$

$=\frac{1}{a}{\int }_{0}^{\infty }{e}^{-\frac{s}{a}\tau }f\left(\tau \right)d\tau$

$=\frac{1}{a}F\left(\frac{s}{a}\right)$

$\tau =at$ の関係から

$\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(at\right)\right\}=\frac{1}{a}F\left(\frac{s}{a}\right)$

## ■証明

$\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(\frac{t}{a}\right)\right\}={\int }_{0}^{\infty }{e}^{-st}f\left(\frac{t}{a}\right)dt$

ここで， $\tau =\frac{t}{a}$  とおくと， $dt=ad\tau$$f\left(at\right)=f\left(\tau \right)$ となり

$\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(\tau \right)\right\}={\int }_{0}^{\infty }{e}^{-sa\tau }f\left(\tau \right)\text{\hspace{0.17em}}·\text{\hspace{0.17em}}ad\tau$

$=a{\int }_{0}^{\infty }{e}^{-sa\tau }f\left(\tau \right)d\tau$

$=aF\left(as\right)$

$\tau =\frac{t}{a}$  の関係から

$\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(\frac{t}{a}\right)\right\}\text{\hspace{0.17em}}$$=aF\left(as\right)$

$\frac{1}{a}\text{\hspace{0.17em}}\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(\frac{t}{a}\right)\right\}$$=F\left(as\right)$

ラプラス変換線形性より

$\frac{1}{a}\text{\hspace{0.17em}}\mathcal{L}\text{\hspace{0.17em}}\left\{f\left(\frac{t}{a}\right)\right\}=\mathcal{L}\text{\hspace{0.17em}}\left\{\frac{1}{a}f\left(\frac{t}{a}\right)\right\}=F\left(as\right)$

ホーム>>カテゴリー分類>>微分>>ラプラス変換>>相似定理

最終更新日： 2023年6月6日